Traditional Chinese medicine in osteoporosis: from pathogenesis to potential activity - Cao, Gang; Hu, ShaoQi; Ning, Yan; Dou, Xinyue; Ding, Chuan; Wang, Lu; Wang, Zeping; Sang, Xianan; Yang, Qiao; Shi, Jiangnan; Hao, Min; Han, Xin (Frontiers in Pharmacology, 2024)
Osteoporosis characterized by decreased bone density and mass, is a systemic bone disease with the destruction of microstructure and increase in fragility. Osteoporosis is attributed to multiple causes, including aging, inflammation, diabetes mellitus, and other factors induced by the adverse effects of medications. Without treatment, osteoporosis will further progress and bring great trouble to human life. Due to the various causes, the treatment of osteoporosis is mainly aimed at improving bone metabolism, inhibiting bone resorption, and promoting bone formation. Although the currently approved drugs can reduce the risk of fragility fractures in individuals, a single drug has limitations in terms of safety and effectiveness. By contrast, traditional Chinese medicine (TCM), a characteristic discipline in China, including syndrome differentiation, Chinese medicine prescription, and active ingredients, shows unique advantages in the treatment of osteoporosis and has received attention all over the world. Therefore, this review summarized the pathogenic factors, pathogenesis, therapy limitations, and advantages of TCM, aiming at providing new ideas for the prevention and treatment of OP.